2020
DOI: 10.3390/cells9030619
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Promotes Early Neural Differentiation in Adult Mesenchymal Stem Cells Through Protein Signalling Pathways

Abstract: Regenerative medicine is a rapidly expanding area in research and clinical applications. Therapies involving the use of small molecule chemicals aim to simplify the creation of specific drugs for clinical applications. Adult mesenchymal stem cells have recently shown the capacity to differentiate into several cell types applicable for regenerative medicine (specifically neural cells, using chemicals). Valproic acid was an ideal candidate due to its clinical stability. It has been implicated in the induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…The cells were harvested for proteomic analysis as per Santos et al [ 27 ] for liquid chromatography-tandem mass spectrometry (LC-MS/MS), at time points of 0, 3, 6 and 24 h post treatment, were completed in biological and technical triplicates. Culture media was collected from each well in 2 mL Eppendorf tubes and stored at −80 °C for later Bioplex and toxicity assays.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cells were harvested for proteomic analysis as per Santos et al [ 27 ] for liquid chromatography-tandem mass spectrometry (LC-MS/MS), at time points of 0, 3, 6 and 24 h post treatment, were completed in biological and technical triplicates. Culture media was collected from each well in 2 mL Eppendorf tubes and stored at −80 °C for later Bioplex and toxicity assays.…”
Section: Methodsmentioning
confidence: 99%
“…Bioplex analysis was performed as per Santos et al [ 27 ] with 500 μL aliquots collected at timepoints and controls as follows: DMEM control, starve, B27 control, 0, 3, 6 and 24 h. The assay was performed using Bioplex human 27-plex (M50-0KCAF0Y Bio-Rad Laboratories, Hercules, CA, USA). The data analysis was completed using DanteR software (DanteR version 1.0.0.10, R version 2.12.0, The R Foundation for Statistical Computing, Auckland, New Zealand) [ 77 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This Special Issue covers research articles investigating various adipose tissues as a source for ASC isolation [ 1 , 2 , 3 ], specific cultures methods to enhance proliferation or viability [ 4 , 5 , 6 , 7 ], and the differentiation capacity [ 8 , 9 , 10 , 11 , 12 ]. Furthermore, other studies highlight aspects of various diseases [ 13 , 14 ], the immunosuppressive potential of ASCs and their derivates [ 15 ] or the in vivo tracking of transplanted ASCs [ 16 ].…”
mentioning
confidence: 99%
“…Others studied various effects of differentiation events induced by differentiation-inducing agents. Using valproic acid, the induced neural differentiation of ASCs was demonstrated by the upregulation of characteristic neuro-specific factors [ 8 ]. Zöller and co-workers showed that collagen I was able to modulate lipogenesis and adiponectin expression, and hypothesized that this could contribute to age-related metabolic disorders [ 10 ].…”
mentioning
confidence: 99%